2013
DOI: 10.1371/journal.pone.0074202
|View full text |Cite|
|
Sign up to set email alerts
|

Telomere Reprogramming and Maintenance in Porcine iPS Cells

Abstract: Telomere reprogramming and silencing of exogenous genes have been demonstrated in mouse and human induced pluripotent stem cells (iPS cells). Pigs have the potential to provide xenotransplant for humans, and to model and test human diseases. We investigated the telomere length and maintenance in porcine iPS cells generated and cultured under various conditions. Telomere lengths vary among different porcine iPS cell lines, some with telomere elongation and maintenance, and others telomere shortening. Porcine iP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 70 publications
(99 reference statements)
0
21
0
Order By: Relevance
“…27,28 Similarly, human and murine induced pluripotent stem cells (iPSCs) are capable of carrying out re-elongation of telomeres in at least some clones, although the telomere length and activity characteristics appear to be clonally unique. [28][29][30][31][32][33] Conversely, the process of differentiation triggers down-regulation of telomerase and initiates telomeric attrition. 34,35 Following the extended cellular division required to form adult tissues, terminally differentiated cell types typically exhibit low or undetectable levels of telomerase activity and shortened telomeres.…”
Section: Telomeres and Pluripotent Stem Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…27,28 Similarly, human and murine induced pluripotent stem cells (iPSCs) are capable of carrying out re-elongation of telomeres in at least some clones, although the telomere length and activity characteristics appear to be clonally unique. [28][29][30][31][32][33] Conversely, the process of differentiation triggers down-regulation of telomerase and initiates telomeric attrition. 34,35 Following the extended cellular division required to form adult tissues, terminally differentiated cell types typically exhibit low or undetectable levels of telomerase activity and shortened telomeres.…”
Section: Telomeres and Pluripotent Stem Cellsmentioning
confidence: 99%
“…42 Similarly, long term self-renewal and teratoma formation in murine and porcine iPSCs with short telomeres are generally impaired. 31,43 In addition, PSCs with short telomeres in a variety of species display mitochondrial dysfunction, 44 impaired neuroectodermal differentiation, 44 uncapping events, and reduction in H3K27me3 distal to telomeres including global hypomethylation which contributes to reactivation of pluripotency genes, 45 and possibly reprogramming transgenes. 31,33,46 Partially reprogrammed iPSCs often show little TERT activation and short telomeres.…”
Section: Telomeres and Pluripotent Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies using extracts from GV stage oocytes or MIIoocytes have shown that oocytes at different stages had distinctive and unique mechanisms for somatic cell reprogramming, which differed from reprogramming techniques used to produce induced pluripotent stem cells with defined transcription factors [66][67][68]. It has been shown that treatment with MII extract could induce at least partial reprogramming in somatic cells [69].…”
Section: Second Metaphase Stage Cytoplasts As Recipientsmentioning
confidence: 99%